2012
DOI: 10.1007/s10384-012-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for primary open-angle glaucoma in South Korea: the Namil study

Abstract: In the Namil study, higher IOP, older age and a history of thyroid disease were significant risk factors for POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 22 publications
(35 reference statements)
3
104
2
6
Order By: Relevance
“…In this (ie, Korean) study, high-tension cases (88.5% of all cases) were primarily recruited, even though normaltension glaucoma (2.7%) is much more prevalent than high-tension glaucoma (0.8%) in the general Korean population. 37 In addition, the average intraocular pressure was 28.2 mm Hg, which was much higher than the average pressure in the previous Japanese study (15.5 mm Hg). 29 Although the effect of the Korean marker rs7098387 on high-tension POAG (OR ¼ 2.2 (1.5-3.1), P ¼ 0.00012) was not much different from that on total POAG (OR ¼ 2.0 (1.4-3.0), P ¼ 0.00038) in this study, it remains to be determined whether the rs7098387 and rs7081455 markers are separately associated with high-tension and normal-tension glaucoma, respectively.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In this (ie, Korean) study, high-tension cases (88.5% of all cases) were primarily recruited, even though normaltension glaucoma (2.7%) is much more prevalent than high-tension glaucoma (0.8%) in the general Korean population. 37 In addition, the average intraocular pressure was 28.2 mm Hg, which was much higher than the average pressure in the previous Japanese study (15.5 mm Hg). 29 Although the effect of the Korean marker rs7098387 on high-tension POAG (OR ¼ 2.2 (1.5-3.1), P ¼ 0.00012) was not much different from that on total POAG (OR ¼ 2.0 (1.4-3.0), P ¼ 0.00038) in this study, it remains to be determined whether the rs7098387 and rs7081455 markers are separately associated with high-tension and normal-tension glaucoma, respectively.…”
Section: Discussioncontrasting
confidence: 51%
“…The demographic and clinical details of the study subjects are summarized in Table 1. The male/female ratio (1.6) was high in the case of this recruitment, as in the general POAG prevalence (gender ratio of 1.4) of Koreans, 37 but there was no attempt to match with control recruitment (gender ratio of 1.0), which would have necessitated an adjustment for gender in the susceptibility association tests.…”
Section: Study Participantsmentioning
confidence: 92%
See 1 more Smart Citation
“…The high prevalence of POAG with normal IOP in Chinese people was reported in the Liwan eye study, which obtained data similar to that found in Japan and Korea. 19,20 Furthermore, as in the Tajimi study, the low average IOP in POAG subjects and the high prevalence of POAG with normal IOP do not mean that IOP was not related to POAG. The average IOP in POAG with high or normal IOP subjects was 25.3 6 6.2 mm Hg or 15.2 6 2.3 mm Hg, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…In East Asia, most patients with open-angle glaucoma have normal tension glaucoma (NTG) (Suzuki et al 2006;Kim et al 2011;Liang et al 2011). Therefore, other etiological factors other than elevated IOP seem to be important for the pathogenesis of glaucoma, particularly in these populations (David et al 1985;Mitchell et al 1999;Wong et al 2000).…”
Section: Introductionmentioning
confidence: 99%